Power and interest on Sumatra’s rainforest frontier: clientelist coalitions, illegal logging and conservation in the Alas valley - McCarthy, J.F. (2002)
This article examines the institutional matrix associated with logging and forest pioneering in a district on Sumatra. It draws together theoretical approaches to develop a framework for analysing the operation of competing forms of institutional power and control. The article argues that the governance of local natural resources and the current epidemic of ‘illegal logging’ can be understood in terms of the particular institutional or socio-political structures found in remote forested areas.